The Role of Anticoagulants in Postoperative Care: Balancing Risk and Benefits in General and Plastic Surgical Patients - Asghar Ali, Noor Sardar Afridi, Aftab Hussain, Hafiz Waqas Ahmed, Mufassar Nishat, Abdul Wali Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Thromboembolic event prevention remains the main application of anticoagulants in postoperative care yet this treatment increases bleeding risks. The maintenance of appropriate risk management between anticoagulation and bleeding stands as an essential requirement particularly for general surgical and plastic surgical patients. The research examines the advantages together with adverse repercussions of anticoagulation therapy in this specific group of patients. Methodology: The research tracked surgical patients from the general and plastic categories throughout a prospective cohort study by monitoring anticoagulated patients and patients who did not receive anticoagulation. The research tracked two primary effects of thromboembolism and bleeding complications as the main results with additional observations regarding wound healing rates and surgical infections and hospitalization times and patient survival statistics. The statistical analysis employed chi-square with t-tests for data evaluation and established p ≤ 0.05 as the level of statistical significance. Results: Anticoagulated patients developed fewer deep vein thrombosis and pulmonary embolism events (p < 0.05) while they experienced more serious bleeding conditions that required medical intervention (p < 0.05). The groups showed no important differences regarding wound healing, surgical site infection rates and healthcare duration after surgery. The only observed deaths occurred within the non-anticoagulated patient group because of pulmonary embolism. Conclusion: Conducting anticoagulation therapy minimizes blood clotting dangers while leading to more bleeding events. The successful postoperative management depends on an individualized risk-based strategy along with a balanced approach. Keywords: Anticoagulation, thromboembolism, bleeding risk, postoperative care, general surgery, plastic surgery